FIRST RECORD OF AEDES ALBOPICTUS IN MICHOACÁN STATE, MEXICO - Ortega-Morales, Aldo I; Morales-Avitia, Isis J; Arque-Chunga, Wilfredo; Ayala-Sulca, Yuri O; Rodríguez-Rojas, Jorge J (Journal of the American Mosquito Control Association, 2025)
During August and September 2024, mosquito collections were conducted in southeastern Mexico, including the state of Michoacán. Species collected in Michoacán included Aedes aegypti, Ae. albopictus, Ae. epactius, Haemagogus sp., and Culex quinquefasciatus. This is the first record of Ae. albopictus in Michoacán state. At present, the expansion of Ae. albopictus includes most states and physiographical regions of Mexico, including the entire Pacific Coast region from Sinaloa to Chiapas states. The Mexican states where Ae. albopictus has not yet been reported are Aguascalientes, Baja California, Baja California Sur, Chihuahua, Durango, Sonora, Tlaxcala, and Zacatecas. Specimens collected during this study were deposited in the Culicidae Collection of the Antonio Narro Autonomous Agrarian University in Coahuila, Mexico.